Interferon‐free therapies for patients with chronic hepatitis C genotype 3 infection: A systematic review. Issue 11 (23rd January 2017) - Gimeno‐Ballester, V.; Buti, M.; San Miguel, R.; Riveiro, M.; Esteban, R.
Summary: Treatment of hepatitis C virus (HCV) infection with genotype 3 remains a challenge. The HCV elimination rate with direct‐acting antivirals (DAAs) is lower than the values reported for other HCV genotypes. In addition, genotype 3‐infected patients have a higher risk of disease progression and hepatocellular carcinoma. The aim of this study was to review the relevant literature concerning the treatment of HCV genotype 3 patients with interferon‐free regimens. A literature search was conducted in the PubMed/Medline, Embase and Web of Science electronic databases. Trials enrolling patients with chronic hepatitis C infection treated with DAAs with or without ribavirin were included. Two investigators independently evaluated the trials for inclusion criteria, risk of bias and data extraction. The primary outcome was sustained virological response (SVR). In total, 323 references were identified, and 29 met the inclusion criteria: 18 general clinical trials, three general observational studies, three studies in patients with decompensated liver cirrhosis and four studies in HIV–HCV‐coinfected patients. Overall, 4068 genotype 3 patients were included. As compared with sofosbuvir and ribavirin for 24 weeks, sofosbuvir/velpatasvir for 12 weeks or sofosbuvir plus daclatasvir plus ribavirin for 12 weeks provided higher SVR rates, particularly in patients with cirrhosis. Treatment of patients with decompensated cirrhosis remains a great challenge. Sofosbuvir/ledipasvir+ribavirin for 12 weeks were associated with an SVR of 85% in these patients. In summary, treatment of HCV genotype 3 patients is improving rapidly, and this population may no longer be considered a difficult‐to‐treat subgroup in the near future.